2006
DOI: 10.1103/physrevlett.96.046101
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Nanohydrodynamics at Liquid-Solid Interfaces Using Thermal Motion

Abstract: We report on a new method to characterize nano-hydrodynamic properties at the liquid/solid interface relying solely on the measurement of the thermal motion of confined colloids. Using Fluorescence Correlation Spectroscopy (FCS) to probe the diffusion of the colloidal tracers, this optical technique -equivalent in spirit to the microrheology technique used for bulk propertiesis able to achieve nanometric resolution on the slip length measurement. It confirms the no-slip boundary condition on wetting surfaces a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
177
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(187 citation statements)
references
References 32 publications
10
177
0
Order By: Relevance
“…Since the EO flow amplification scales as (1 + bκ), and b can be of the order of tens of nanometers [9,10,11,12], for typically nanometric Debye length an order of magnitude enhancement might be expected.…”
Section: Electro-osmotic Velocity In Eigendirectionsmentioning
confidence: 99%
“…Since the EO flow amplification scales as (1 + bκ), and b can be of the order of tens of nanometers [9,10,11,12], for typically nanometric Debye length an order of magnitude enhancement might be expected.…”
Section: Electro-osmotic Velocity In Eigendirectionsmentioning
confidence: 99%
“…This length being typically nanometric in standard aqueous electrolytes, one can anticipate that the dynamics of charged systems should probe hydrodynamics in the nanometric vicinity of charged solid surfaces. One can in particular expect an interesting coupling with nanometric slippage, as predicted theoretically for neutral surfaces [2] and evidenced experimentally [5,8]. Furthermore, hydrophilic and hydrophobic surfaces exhibit different electric properties [12], and the coupling between pure wetting effects and "charge-mediated" effects is a priori subtle and remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…[2,5,6,8,9]). Moreover, it has been shown that this violation of the usual no-slip BC is controlled by the wetting properties of the fluid on the solid surface: while the no-slip BC is fulfilled on hydrophilic surfaces, a finite velocity slip is measured on hydrophobic surfaces [2,5,8], originating in a low friction of the liquid at the wall.…”
Section: Introductionmentioning
confidence: 99%
“…As a guide, the dotted line shows the theoretical prediction for bZ100 nm slip length, illustrating the method sensitivity. Graph is taken from Joly et al (2006). than 1 mm) makes such a measurement rather challenging.…”
Section: Micro-and Nanovelocimetrymentioning
confidence: 99%
“…The results for different wetting properties of the solid substrates lead to measurable differences in the diffusion coefficient, allowing us to deduce the corresponding surface slippage. Details of the set-up are reported by Joly et al (2006). Below, we discuss only the most pertinent features of the experimental procedure.…”
Section: Thermal Motion Of Confined Colloidsmentioning
confidence: 99%